Implementasi Strategi Saluran Pemasaran Digital Asuransi Kesehatan PT XYZ Insurance - Lianel, Lavenia Mulyana; Nurvita, Silvia (Unitri Press, 2025)
The development of digital technology continues to transform how the insurance industry interacts with customers. PT XYZ Insurance utilizes digital marketing strategies to enhance brand visibility and effectively reach more potential customers. This study aims to analyze how the company implements digital strategies in marketing insurance products to improve its competitiveness in the market. Using a descriptive method, this research was conducted through observation, interviews, and document analysis. The findings indicate that PT XYZ Insurance relies on six main channels: Search Engine Marketing (SEM), social media, email marketing, digital content, video marketing, and marketplace and e-commerce. This strategy has been effective in building brand awareness and increasing customer engagement. However, the company still faces challenges such as high marketing costs, suboptimal customer interaction levels, and the complexity of product education. Based on SWOT analysis, PT XYZ Insurance can optimize data-driven marketing, enhance interactive digital content quality, and integrate technology to Strengthen its competitive advantage in the insurance industry. Abstrak Perkembangan teknologi digital terus mengubah cara industri asuransi berinteraksi dengan pelanggan. PT XYZ Insurance memanfaatkan strategi pemasaran digital untuk meningkatkan visibilitas merek dan menjangkau lebih banyak calon nasabah secara efektif. Penelitian ini bertujuan untuk menganalisis bagaimana perusahaan menerapkan strategi digital pada pemasaran produk asuransi agar dapat bersaing di pasar. Menggunakan metode deskriptif, penelitian ini dilakukan dengan observasi, wawancara, dan analisis dokumentasi. Pada penelitian hasil yang didapat menunjukkan bahwa PT XYZ Insurance mengandalkan enam saluran utama, yaitu Search Engine Marketing (SEM), social media marketing, email marketing, content marketing, video marketing, serta marketplace dan e-commerce. Strategi ini cukup efektif guna membangun brand awareness dan membantu meningkatkan engagement pelanggan. Namun, perusahaan masih menghadapi tantangan seperti biaya pemasaran yang tinggi, tingkat interaksi pelanggan yang belum optimal, serta kompleksitas edukasi produk. Berdasarkan analisis SWOT, PT XYZ Insurance dapat mengoptimalkan pemanfaatan data pemasaran, meningkatkan kualitas konten digital yang lebih interaktif, serta mengintegrasikan teknologi untuk memperkuat daya saingnya di industri asuransi.